New species of the jumping spider genus Ilargus Simon, 1901 (Araneae: Salticidae), with notes on all Argentinean species - Rubio, Gonzalo Daniel (2022)
A study of the jumping spider genus Ilargus Simon, 1901 from Argentina, with live colour photographs of all recorded species, is presented. Two new species, I. delnoa sp.n. (♂♀) and I. carinae sp.n. (♂), are described. All the Ilargus species occurring in the country are diagnosed and provided with new geographic records, and a potential distribution of the genus is modelled. Ilargus is known from at least two ecoregional sectors of Argentina.